Sagittal spinal curvatures in adolescent male basketball players and non-training individuals - a two-year study - Grabara, M. (Science & Sports, 2016)
Objective: To compare changes in anteroposterior spinal curvatures in young male basketball players and non-training controls over a 2-year period. Methods: The study included 10 basketball players and 11 non-training males. At the start of the study, all participants were aged 13; they underwent three anteroposterior spinal curvature measurements at baseline and years 1 and 2 of the study. A Rippstein plurimeter was used to determine anteroposterior spinal curvatures. Results: Basketball players and their non-training peers only differed regarding the 1st quantification of lumbar lordosis (P < 0.05). Consecutive measurements of thoracic kyphosis (P < 0.05) and lumbar lordosis (P < 0.05) in basketball players turned out to be significantly different. Non-athletes only exhibited significant differences in the thoracic kyphosis angle (P < 0.05). Conclusions: The shape of anteroposterior spinal curvatures has changed in both basketball players and non-athletes; however, the trends of these changes were different. Basketball players exhibited age- and training time-related flattening of the thoracic spine while non-athletes showed deepening of the thoracic kyphosis. This might evidence some effect of regular basketball training on the shape of anteroposterior spinal curvatures.